Efek suplementasi Î²-carotene terhadap kolesterol total, trigliserida dan malondialdehid pada tikus sprague dawley yang diabet - Ermawati, Devi; Rachmawati, Banundari; Widyastiti, Nyoman Suci (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background : diabetes mellitus (DM) is associated with increased total cholesterol and triglyceride, also well characterized by increased malondialdehyde production. Î²-carotene has antioxidant activity, glycemic and lipid control. Objective : to analyze the effect of Î²-carotene on total cholesterol, triglyceride and MDA on diabetic Rattus norvegicus sprague dawley. Methods : thirty rats were randomly divided into 5 groups : 1 (STZ), 2 (STZ+Î²-carotene 1 mg/kg BW), 3 (STZ+Î²-carotene 10 mg/kg BW), 4 (STZ+Î²-carotene 20 mg/kg BW), 5 (normal). Streptozotocin induced intraperitoneal 40 mg/kg BW. Î²-carotene was given by nasogastric tube on alternate days within thirty days. Blood glucose level was measured by GOD-PAP, total cholesterol by CHOD-PAP, triglyceride by GPO and MDA by ELISA with TBARS methods. Hypothesis test used one way anova then followed by post hoc bonferroni to analyze the efficient dose effect. Results : there was a significant difference of total cholesterol (p=0.002) after Î²-carotene 10 mg/kg BW supplementation on alternate days within 30 days orally. Î²-carotene 10 mg/kg BW was the most efficient dose to lowering total cholesterol. There were significant differences of triglyceride (p=0.0001) and MDA (p=0.0001) after Î²-carotene 1, mg/kg BW, 10 mg/kg BW and 20 mg/kg BW supplementation on alternate days within 30 days orally. Î²-carotene 10 mg/kg BW was the most efficient dose to lowering triglyceride, while 20 mg/kg BW to lowering MDA. Conclusion : Î²-carotene 10 mg/kg BW is the most efficient dose to lowering total cholesterol and triglyceride. Î²-carotene 20 mg/kg BW is the most efficient dose to lowering MDA.